Understanding the factors associated with married women's attitudes towards wife-beating in sub-Saharan Africa - Betregiorgis Zegeye; Comfort Z. Olorunsaiye; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Eugene Budu; Abdul-Aziz Seidu; Sanni Yaya (BMC, 2022)
Abstract Background Intimate partner violence remains a major public health problem, especially in countries in sub-Saharan Africa. We examined the factors associated with married women's attitudes towards wife-beating in sub-Saharan Africa. Methods We used Demographic and Health Survey data of 28 sub-Saharan African countries that had surveys conducted between 2010 and 2019. A sample of 253,782 married women was considered for the analysis. Bivariate and multivariate logistic regression analyses were carried out, and the results were presented using crude odds ratio (cOR) and adjusted odds ratio (aOR) at 95% confidence interval. Results The pooled result showed about 71.4% of married women in the 28 countries in this study did not justify wife-beating. However, the prevalence of non-justification of wife-beating varied from 83.4% in Malawi to 17.7% in Mali. Women's age (40-44 years-aOR = 1.61, 95% CI 1.16-2.24), women's educational level (secondary school-aOR = 1.47, 95% CI 1.13-1.91), husband's educational level (higher-aOR = 0.55, 95% CI 0.31-0.95), women's occupation type (professional, technical or managerial-aOR = 1.66, 95% CI 1.06-2.62), wealth index (richest-aOR = 5.52, 95% CI 3.46-8.80) and women's decision-making power (yes-aOR = 1.39, 95% CI 1.19-1.62) were significantly associated with attitude towards wife-beating. Conclusion Overall, less than three-fourth of married women in the 28 sub-Saharan African countries disagreed with wife-beating but marked differences were observed across socio-economic, decision making and women empowerment factors. Enhancing women's socioeconomic status, decision making power, and creating employment opportunities for women should be considered to increase women's intolerance of wife-beating  practices, especially among countries with low prevalence rates such as Mali.